Reproductive health problems and their awareness among adolescent girls: a clinical study - Sharma, Sumedha; Sharma, Puja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The adolescent girls constitute a heterogeneous group who are at risk of various reproductive and gynecological problems. A number of health schemes are already aimed at targeting the needs of this special population. This study was aimed at identifying the special needs of this population group in respect of medical and reproductive health so as to provide a feedback for ongoing health schemes. Methods: This study was a cross sectional analytical study conducted among adolescent girls attending various government and public schools in Lucknow city and adolescent girls presenting to Gynecology OPD of Queen Mary’s Hospital for various complaints in a span of one year from June 2007 to June 2008. After taking consent, the girls were subjected to a questionnaire consisting of epidemiological parameters and questions regarding menstruation, pregnancy, birth spacing, contraception, abortion, RTI/STD, sex education. This data was later analysed. Those presenting to the OPD of Queen Mary Hospital were subjected to further examination and tests depending on their complaints. Results: A total of 1127 adolescent girls in the age group of 10-19 consented and were included in the study. Awareness regarding the contraceptive methods available was present in only 57.8%. 14% (164) girls were aware of reproductive tract infections and sexually transmitted diseases. However, 61% (687) girls were aware about HIV/AIDS in particular. The mean age at menarche was 11.9±1.0 years. 21.5% had some menstrual problem. There were 34 cases of teenage pregnancy. Conclusions: Our study revealed substantial lacunae in the knowledge and attitude of young adolescent girls towards reproductive and sexual health. Despite various targeted health programs from the government, there is a still a need to further our efforts to improve access to health care and adopt methods to improve awareness regarding the health issues of adolescents.